Heart and Mitochondria: Pathophysiology and Implications for Cardiac Surgeons - Niemann, Bernd; Schwarzer, Michael; Rohrbach, Susanne (The Thoracic and Cardiovascular Surgeon, 2018)
Excluding the heart from systemic circulation during cardiac surgery renders the myocardium ischemic, resulting in cardiac damage. In addition, another hit to the myocardium will occur upon restoration of blood flow, in the reperfusion phase. Experimental data from animal models have revealed that loss of cardiac metabolic flexibility and mitochondrial dysfunctions contributes to contractile impairment in hypertrophied, failing, obese, and diabetic hearts. Such diseased hearts are prone to myocardial ischemia–reperfusion (I/R) injury. Although analyses in human cardiac samples are not as comprehensive as animal data, similar disease-associated metabolic and mitochondrial changes exist. Considering increasing age and comorbidities in patients nowadays, it is not surprising that I/R injuries remain a major cause of morbidity and mortality after cardiac surgery. Mitochondria have emerged as critical targets but also key regulators of myocardial I/R injury, and the extent of mitochondrial damage is a major determinant of myocardial I/R injury. Although cardioprotective mechanisms are diverse, many come together and involve steps at the point of mitochondria. We will, therefore, provide a description of mitochondrial alterations observed in various cardiac disease states and discuss the current experimental knowledge of the role of mitochondria in I/R and of potential protective mechanisms against myocardial I/R injury involving mitochondria. Within this review, we will focus on the protection against I/R injury conferred by caloric restriction (CR) and by ischemic conditioning. Further research is needed to establish whether strategies targeting mitochondria, which have been proposed from preclinical studies, could be translated into cardioprotective therapies against I/R injury in patients.
Keywords: mitochondria; ischemia–reperfusion; metabolism; caloric restriction; ischemic conditioning